EVALUATION OF INJECTION MOLDING PROCESS PARAMETERS ON THE QUALITY OF BRAKE FLUID RESERVOIR CAP PRODUCTS USING MOLDFLOW SIMULATION - Adinda Rahmah Shalihah; Aditya Bagja Subarkah; Farras Novyansyah; Irfan Fadillah; Ammar Fathi Muhadzab; Hafizh Maulana Alfath; Ulima Adristi Azis; Hikari Qurrata’ain Nurhadi (Otopro, 2026)
This study aims to analyze the effect of melt temperature and mold surface temperature variations on the quality of the motorcycle brake fluid reservoir cap using Autodesk Fusion simulation. Three parameter variations were applied: 260°C/80°C, 220°C/50°C, and 180°C/20°C, while other process parameters were kept constant. The evaluation focused on fill confidence, weld lines, sink marks, and warpage. The results show that all conditions achieved 100% fill confidence with a filling time of 0.53 seconds. However, higher temperatures reduced weld lines but increased sink marks and warpage. Conversely, lower temperatures minimized deformation but increased the number of visual defects. The medium temperature condition provided the best balance between visual quality and dimensional stability. Therefore, the 220°C/50°C condition is recommended as optimal